Identification of Important Issues in Aerotropolis Infrastructure Development: A Case Study of Yogyakarta International Airport - Pratama, Raden Prabowo Yoga; Rijanta, R.; Muta’ali, Lutfi (Jurnal Multidisiplin Madani, 2023)
Yogyakarta International Airport (YIA) infrastructure development supports the aerotropolis concept, an airport designed to be an independent city with many business activities to provide sustainable benefits for the surrounding community. However, some sensitive issues regarding the development of YIA's aerotropolis infrastructure are found currently, which impacts the response and development of the community in the area. This research aims to identify important issues that have developed in the observed area due to the development of the airport's infrastructure. This is qualitative and explorative research, carried out by observation and literature study to identify the issues that occur. The USG method is used to determine important issues found in the observation area, which leads to the important issues that can be determined as priorities in the area. The results show that each region has one important issue in common, even though these regions have different regional characteristics. Important issues in each region around YIA's infrastructure are further discussed in this article. Important issues in each region around YIA's infrastructure are further discussed in this article